Aging and Mental Health in a Longitudinal Study of Elderly Costa Ricans - Rosero Bixby, Luis (2015)
Geriatric depression and cognition impairment, including memory loss, are common neuropsychiatric disorders at old age. Diagnosing these conditions in the context of a general population-based survey conducted by nonmental health specialists is challenging. The effect of aging on an individual’s mental health is not always mirrored in the prevalence of mental disorders of the population by age. Changes over time and across cohorts, as well as survival selection, affect the comparison of individuals at different ages. Longitudinal studies that follow the same individuals over time allow a better assessment of the effect of age on mental health. The Costa Rican Longevity and Healthy Aging Study (CRELES) includes a panel of elderly people that provides a rare opportunity of documenting mental health and aging in a middle-income country.